Comparison of the Effectiveness of Compassion-Based and Mindfulness-Based Therapies on Dysfunctional Communication Beliefs in Women with Multiple Sclerosis - Moeinzadeh , Nazila; Souri, Ahmad; Seadatee Shamir, Aboutaleb (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: This study aimed to compare the effectiveness of mindfulness-based and compassion-based therapies in reducing dysfunctional communication beliefs among women with multiple sclerosis (MS). Methods and Materials: The study employed a quasi-experimental design with a pretest-posttest format and included two experimental groups and one control group. A total of 36 women with MS were selected through purposive and convenience sampling based on predefined inclusion and exclusion criteria and were randomly assigned to mindfulness (n = 12), self-compassion (n = 12), and control (n = 12) groups. The intervention programs included eight weekly sessions for each experimental group, while the control group received no treatment. Dysfunctional communication beliefs were measured using the Epstein and Eidelson Communication Beliefs Questionnaire administered at pretest and posttest. Data were analyzed using paired t-tests, multivariate analysis of covariance (MANCOVA), and Tukey’s post hoc test to assess within- and between-group differences. Findings: The results revealed significant reductions in all subscales of dysfunctional communication beliefs in both the mindfulness and self-compassion groups from pretest to posttest (p < .001), with no significant change observed in the control group. MANCOVA results showed significant between-group differences in posttest scores across all variables (p < .001). Tukey’s post hoc analysis indicated that the mindfulness group exhibited the greatest improvement, followed by the self-compassion group, while the control group performed the worst. Conclusion: Both mindfulness-based and compassion-based therapies are effective in reducing dysfunctional communication beliefs in women with MS, with mindfulness demonstrating superior efficacy. These findings support the integration of psychological interventions targeting relational cognition into the treatment of individuals with chronic illnesses to enhance their emotional and interpersonal well-being.